The use of the lecture, discussion and interactive methods at university; implicationsof students performansce in english language - Khalid Kamil Abdulbaki (2020)
The current research deals with the perceptions of non-native students at a university college in Oman on the use of the lecture, discussion and interactive methods in teaching English. The aim is to verify the method which may assist satisfactorily in achieving its goals and objectives in improving students' language skills, developing their cognitive abilities and enhancing their personal growth. While university students' views are significant in the choice of a method of teaching, there is a gap in literature to be filled. The researcher has not fallen upon a previous research that dealt with the issue of which method of teaching is viewed by students as effective and appropriate for their learning as well as the reasons behind these views. The present study, thus, employs the quantitative approach as it is most appropriate through conducting and analyzing students' questionnaires related to the lecture, discussion and interactive methods of teaching. The findings of this research indicate that the discussion and interactive methods are highly viewed by students while the lecture gets a lower mean. Moreover, weak students incline to the lecture method in contrast to average, good and very good students. The implications of the use of the discussion and interactive methods could be extended to the social side of education. Students exchange ideas, suggestions and feelings which contribute to strengthening their relationships as colleagues. They would not affect the role of the lecturer as an educator and leader, yet they could create an active and enjoyable atmosphere in class.